How are we measuring physical activity and sedentary behaviour in the four home nations of the UK? A narrative review of current surveillance measures and future directions - Strain, Tessa (Br J Sports Med, 2020)
BACKGROUND/OBJECTIVES: To explore and describe the comparability between the surveys of the UK home nations (England, Northern Ireland, Scotland, Wales) that monitor compliance with the Chief Medical Officers’ physical activity (PA) recommendations. We also suggest ways to improve the UK national PA and sedentary behaviour (SB) surveillance systems. METHODS: We identified national surveys that monitor PA and SB through searching UK-wide and devolved administration websites, the Global Observatory for Physical Activity Country Cards and the Active Healthy Kids Report Cards. Subsequently, we extracted information from survey documentation on the survey commissioners and contractors, method of administration, current questionnaire details relevant to the PA recommendations, questionnaire changes over the previous decade and the most recent prevalence figures. RESULTS: For adults and older adults, five surveys assess the moderate-to-vigorous PA (MVPA) recommendation, three assess muscle strengthening and three assess SB. For older adults only, three assess balance and co-ordination. For children, seven assess MVPA, none assess muscle strengthening and five assess SB. Only one survey reports on the under 5 PA recommendation. There is no part of the recommendations for which comparable estimates can be calculated across all four home nations. The greatest variation is among the SB questions and reporting. No survey has regularly used device-based measures. CONCLUSION: UK surveillance of the PA recommendations is complex, undertaken separately in the home nations, using multiple surveys that cover adults and children separately. We recommend that the costs and benefits of harmonising the existing questionnaires are considered, along with the potential introduction of device-based measures.